Individual health related applied activity in special health group girl-students' way of life in the process of their studying - L.A. Bartnovskay; M.D. Kudryavtsev; V.M. Kravchenko; A.Yu. Osipov; L.A. Baranovskaya; V. V. Ignatova (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: to find out actual life style of special health group girl students in context of their individual health strengthening and improvement, as well as to assess their demands in physical culture practicing. Material: as the object of the research we determined different kinds of leisure and day regime of girl students with weak health (n=300). We analyzed the structure of personality's leisure time: reading, creative work, participation in social life, cultural progress of personality, time expenses for health values. Results: we have found that girl students have insignificant demand in individual health related applied activity. We note noticeable minority of girl students, practicing physical culture often. The regime of educational work is a reason of girl students' asthenic state. Conclusion: The received data witness about absence of constructive girl students' efforts, directed at health improvement. Independently girl students do not show physical activity oriented on health improvement. Day regime will be real and feasible, if it is flexible and considers unexpected circumstances.